ANTESEDEN NILAI PERSEPSIAN KONSUMEN PRODUK PETUALANGAN - Zunan Setiawan; Muhammad Ali Fikri (BALANCE: Economic, Business, Management and Accounting Journal, 2016)
ABSTRACT  This study examines the relationship of factors that affect the perceived value of adventure products including novelty, enjoyment, and price. Testing factors that influence the perceived value of adventure products in research using multiple regression analysis. The respondents of this study are 310 individuals who have conducted group adventure tours in the past year in Yogyakarta province. Characteristics of participants are predominantly based on sex, male, age 21-50 years and employment background, ie employees of private companies. This study reveals that pleasure and novelty are factors that have a positive influence on the value of perceptions. Meanwhile, prices have a negative effect on the value of perceptions. Study suggestions and implications are also discussed. The results showed novelty, pleasure, and price factor for individuals who do adventure tourism rafting adventure products have a significant influence on the value of perceptions of adventure products. Keywords                   : novelty, pleasure, price, and value of perceptionsCorrespondence to       : zoonan46@gmail.com, zunan.setiawan@mm.uad.ac.idm.alifikri77@yahoo.com  ABSTRAK  Studi ini menguji hubungan faktor-faktor yang mempengaruhi nilai persepsian produk petualangan meliputi kebaruan, kenikmatan, dan harga.  Pengujian faktor-faktor yang mempengaruhi nilai persepsian produk petualangan dalampenelitian menggunakan analisis regresi berganda.Responden studi ini adalah 310 individu yang telah melakukan wisata petualangan secara berkelompok dalam satu tahun terakhir di provinsi Yogyakarta. Karakteristik partisipan didominasi berdasarkan  jenis kelamin yaitu laki laki, usia yaitu 21-50 tahun dan latar belakang pekerjaan yaitu karyawan perusahaan swasta. Studi ini mengungkapkan bahwa kenikmatan dan kebaruan menjadi faktor yang mempunyai pengaruh positif pada nilai persepsian. Sedangkan, harga mempunyai pengaruh negatif pada nilai persepsian. Saran dan implikasi studi juga didiskusikan.Hasil penelitian menunjukanfaktor kebaruan, kenikmatan,dan harga bagiindividu yang melakukan wisata petualangan produk petualangan arung jeram mempunyai pengaruh signifikan terhadap nilai persepsianproduk petualangan.Kata Kunci : kebaruan, kenikmatan, harga, dan nilai persepsianKorespondensi : zoonan46@gmail.com, zunan.setiawan@mm.uad.ac.idm.alifikri77@yahoo.com